Internetworking Technologies Handbook, Fourth Edition (Cisco Press, 2003)
The updated edition of the best-selling all-in-one networking reference provides coverage of essential and cutting-edge technologies Concise overviews of technologies essential to networking professionals at all levels, from novice to expert. New chapters include coverage of important topics like VoIP and EAP Coverage of cutting edge technologies like optical networking and storage Authored by Cisco Systems, worldwide leader in networking for the Internet. Internetworking Technologies Handbook, Fourth Edition, is a comprehensive reference that enables networking professionals to understand and implement contemporary internetworking technologies. Master the terms, concepts, technologies, and devices used in today's networking industry. Learn how to incorporate internetworking technologies into a LAN/WAN environment. Complete with new and updated chapters on security, storage, optical networking, scalability, and speed, this book is a complete and up-to-date reference to the topics that are essential to all networking professionals, regardless of expertise. Readers will obtain a greater understanding of LAN and WAN networking, particularly the hardware, protocols, and services involved. Fundamental technology information is provided on a broad range of integral systems and services, including detailed descriptions, review questions to ensure concept comprehension and retention, and additional resources for further study. Coverage is also extended not only to new networking concepts, but also to older, legacy systems, providing a more realistic picture of the real-world networking environments in which professionals operate. Tools and guidelines for optimizing system performance will increase productivity and improve efficiency, helping the reader make more intelligent, cost-efficient decisions for their networks. Cisco Systems, Incorporated is the worldwide leader in networking for the Internet. Cisco solutions, which include industry-leading publications from Cisco Press, educate and a provide competitive advantage to customers through more efficient and timely exchange of information, leading to cost saving, process efficiencies, and closer business relationships. These solutions form the networking foundation for many organizations worldwide.